Tradisi Upacara Memayu dan Ider-Ideran Trusmi Kabupaten Cirebon Jawa Barat - Neneng Lestari (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
This paper aims to reveal the historical background of the emergence of traditions and ceremonies memayu and ider - ideran Trusmi, and the reason why the tradition still survives and sustainable amid modern society has today. To discuss both the subject matter, the author uses the theory of functionalism Bronislow Malinowski. Data were collected through observations, interviews and documentation. The approach used is qualitative method. From the results of this study found that Trusmi name is formed from two words, which continues and spring means constantly growing. The origins of this name originated from the story of Ki Gede Bambangan who was sitting in front of his cabin after cleaning the yard of grass. Suddenly there are greetings that do not know exactly where it comes from that voice. Then miraculously suddenly all the grass and weeds that had already cleared it grows back so pruning becomes useless. When he looked around with astonishment mingled irritation, suddenly, two men are walking towards him while greeting,